2016
DOI: 10.1016/s2213-2600(15)00521-4
|View full text |Cite
|
Sign up to set email alerts
|

E-cigarettes and smoking cessation in real-world and clinical settings: a systematic review and meta-analysis

Abstract: Summary Background Smokers increasingly use e-cigarettes for many reasons, including attempts to quit combustible cigarettes and to use nicotine where smoking is prohibited. We aimed to assess the association between e-cigarette use and cigarette smoking cessation among adult cigarette smokers, irrespective of their motivation for using e-cigarettes. Methods PubMed and Web of Science were searched between April 27, 2015, and June 17, 2015. Data extracted included study location, design, population, definiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
564
3
23

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 791 publications
(637 citation statements)
references
References 57 publications
(100 reference statements)
14
564
3
23
Order By: Relevance
“…Reducing tobacco use through campaigns that depict cigarette smoking as undesirable and harmful has been implemented; however, the promotion of e-cigarettes threatens this with the risk of increasing nicotine addiction [120]. A recent systematic review also found no strong evidence for e-cigarettes as a smoking cessation tool [121]. Urgent legislation and regulation of e-cigarettes is required to prevent another form of nicotine addiction targeted at vulnerable groups [122].…”
Section: Resultsmentioning
confidence: 99%
“…Reducing tobacco use through campaigns that depict cigarette smoking as undesirable and harmful has been implemented; however, the promotion of e-cigarettes threatens this with the risk of increasing nicotine addiction [120]. A recent systematic review also found no strong evidence for e-cigarettes as a smoking cessation tool [121]. Urgent legislation and regulation of e-cigarettes is required to prevent another form of nicotine addiction targeted at vulnerable groups [122].…”
Section: Resultsmentioning
confidence: 99%
“…In theory, a product that can deliver nicotine like a cigarette without the toxins found in smoke could be used instead of cigarettes would be a welcome invention 5, 6, 7. However, concerns have been raised about whether e‐cigarettes are an effective cessation aid or if they would actually reduce successful quitting by adult smokers, whether they are safe to use, and if they may be a gateway into smoking for youth 8, 9, 10. Most recently the popularity of the Juul e‐cigarette among high school and college students who have no intention of smoking has raised concerns about the risk of nicotine addiction in non‐smokers and its long‐term health effects 11…”
Section: Introductionmentioning
confidence: 99%
“…However, these interventions differ in their cost‐effectiveness and may also be associated with unintended consequences. For example, tax increases may create illicit markets 11, 12, while e‐cigarettes may prevent certain smokers from quitting 13. Compared with the United Kingdom 14, smoking cessation aids are used less frequently in Germany 15, 16, while the smoking prevalence (18.0 versus 24.5%) is higher 17, 18.…”
Section: Introductionmentioning
confidence: 99%